2018
DOI: 10.20546/ijcmas.2018.701.225
|View full text |Cite
|
Sign up to set email alerts
|

Brucellosis in Sheep and Goats and its Serodiagnosis and Epidemiology

Abstract: Journal homepage: http://www.ijcmas.com Brucellosis is an important zoonotic disease globally that causes huge economic losses to the livestock owners and is of public health significance. Brucellosis in animals is endemic in India. In sheep and goats, Brucellosis is mainly caused by Brucella melitensis whereas Brucella ovis causes the disease in sheep. The symptoms in infected sheep and goats are abortions, stillbirths and the birth of weak offsprings. Animals that abort may retain the placenta. Sheep and goa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 80 publications
0
13
0
Order By: Relevance
“…In the current study, as antibodies to Brucella were confirmed by testing with an RBT and an iELISA and the results interpreted in series, it is assumed that seropositivity resulted from natural infection rather than a serological response to prior vaccination. Aborted foetal and placental material resulting from infection with Brucella can lead to significant contamination of the environment resulting in disease spread to other ruminants [ 39 ]. This large environmental burden may overcome the immunity induced by vaccination [ 40 ]; however, in the current study location, it is also possible that the vaccine was not administered appropriately or was not maintained in a manner to confirm its efficacy due to poor veterinary services and infrastructure in Iraq [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, as antibodies to Brucella were confirmed by testing with an RBT and an iELISA and the results interpreted in series, it is assumed that seropositivity resulted from natural infection rather than a serological response to prior vaccination. Aborted foetal and placental material resulting from infection with Brucella can lead to significant contamination of the environment resulting in disease spread to other ruminants [ 39 ]. This large environmental burden may overcome the immunity induced by vaccination [ 40 ]; however, in the current study location, it is also possible that the vaccine was not administered appropriately or was not maintained in a manner to confirm its efficacy due to poor veterinary services and infrastructure in Iraq [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…B. ovis infection was confirmed in different countries such as New Zealand [17], Romania [18], Croatia [19.20], Serbia [21], Brazil [22], Argentina [23], India [12,24], France [25] and Turkey [10], while some countries report never having recorded it as in Italy [26], Iran [27], and Canada [28]. In this study, the percentage of negative samples were higher than the positive samples, which can be attributed to either to trauma or to the presence of many species of bacteria causing epididymo-orchitis in ram [2,4].…”
Section: Discussionmentioning
confidence: 99%
“…In India, the brucellosis prevalence rate in cattle and buffaloes has been reported as 8.3 and 3.6%, respectively [ 4 ]. Earlier reports about brucellosis in small ruminants showed a 7.9 % prevalence rate in sheep and 2.2 % in goats [ 5 ]. The threat of brucellosis is severe in rural areas where India’s more than 65 % population lives in close contact with the large domestic animal population (512.05 million approx.).…”
Section: Introductionmentioning
confidence: 99%